Promoting language development in physically disabled adults through sports: The content and language integrated learning method - Bekirogulları, Hasan; Burgul, Nazım; Yagcı, Emete (Frontiers in Psychology, 2022)
This study reports on the outcomes of a qualitative study which explores the perceptions of ten wheelchair basketball players of the implementation of a content and language integrated learning (CLIL) program. The participants were all members of the official wheelchair basketball team of the Sports Federation for the Disabled in North Cyprus. They were all young adults (18–35 years old) and their level of English language proficiency ranged from elementary to beginner. After a 4-month CLIL intervention period, the data were elicited through individual interviews from the participants. A qualitative analysis of the textual data revealed the themes such as improved self-image, high motivation, developed social skills, and better speaking skills in the target language. The results have a few practical implications for English such as foreign language teachers, sports coaches, and local disability committees.